Using “Jas-To-Bloom” to Improve Year 3 Pupils’ Ability in Writing Simple Sentences - Wei Yin, Loh; Mohamad, Maslawati (Opción, 2019)
This study aims to explore the use of ‘Jas-To-Bloom’ as a strategy in improving writing ability. A case study was carried out to investigate the use of ‘Jas-To-Bloom’ in improving Year 3 pupils’ ability in writing. Data was collected via a series of pre-test and post-test, interview with five participants, field notes written by the researcher and document analysis of lesson plans. The results reveal that the use of ‘Jas-To-Bloom’ helps to improve pupils’ ability in writing. The result also shows that the pupils could develop more ideas in writing and able to write their ideas in simple sentences.